Prvi teritorialni travniški vrabci Passer hispaniolensis v Sloveniji - Vrezec, Al (Acrocephalus, 2000)
In 1999, the presence of Spanish Sparrows Passer hispaniolensis was established, in breeding season, at two localities in the sub-Pannonian zoogeographical region of Slovenia. In May and June 1999 a male was observed at Bizeljsko (Kozjansko Park, spodnje Posavje, E Slovenia; 160 m a.) whilepiling up nest material in the nests of House Martins Delichon urbica as well as courting and behaving territorially. On July 4th 1999, on the other hand, a male was observed at Apače (Dravsko polje, Podravje, NE Slovenia; 250 m a.) on the nest of White Stork Ciconia ciconia. Both males were in summer plumage and in the company of House Sparrows Passer domesticus. The localities are situated in a suburban village environment. The authors believethat the presence of territorial Spanish Sparrows in Slovenia could be a sign of a further expansion of this bird's breeding range towards the north.
Keywords: Ornitologija; Vrabci; Bizeljsko; Lower Sava Valley; Posavje; ptice; bird; gnezdenje